Method for preparing porous honeycomb polymer material

By using microemulsion as pore-forming agent in polymer PVDF-HFP, using non-solvent phase separation method and stirring speed control, the problems of contamination and high cost of chemical reagents in the prior art are solved, and porous honeycomb polymer materials are realized The efficient preparation of the product improves porosity and reduces production costs, and is suitable for applications in multiple fields.

CN119241900APending Publication Date: 2025-01-03GUILIN UNIV OF ELECTRONIC TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411357382.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

In the existing preparation methods for porous polymer materials, chemical reagents, as pore-forming agents, have problems of pollution of the environment and high costs, and it is difficult to regulate the pore structure.

Method used

Using microemulsion as pore-forming agent, deionized water and glycerol were introduced into the polymer PVDF-HFP by non-solvent phase separation method, and the porous structure was formed by controlling the phase separation and stirring speed, avoiding solvent replacement and respiration pattern method. The solvent volatilization process achieves precise regulation of pore size and porosity.

Benefits of technology

Achieve environmentally friendly, low-cost, easy to commercially produce porous honeycomb polymer materials, with a 30% increase in porosity, a 35% decrease in cost, a 80% shortening of production cycles, and is shown in the fields of biosensing, drug controlled release and energy storage Excellent performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241900A_ABST
    Figure CN119241900A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a porous honeycomb polymer material, which is a non-solvent phase separation method. The microemulsion (consisting of deionized water and glycerol) is introduced into the polymer PVDF-HFP as a pore-forming agent, and the liquid phase of the microemulsion and the gel phase of the polymer PVDF-HFP are separated by utilizing different volatilization temperatures of various solvents. According to the method, a porous structure is formed by utilizing incompatibility among different phases, and the porous honeycomb polymer material prepared by the method not only can show unique advantages in the fields of biosensing, drug controlled release, environmental monitoring and the like, but also can show excellent electrochemical performance in the field of energy storage, and has a good application prospect. And the method can also be applied to the fields of semi-solid and solid lithium ion batteries, sodium ion batteries and the like. The method is a simple, green and controllable porous honeycomb polymer material preparation method with commercial application potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of energy storage material and film material preparation, and in particular to a method for preparing a porous honeycomb polymer material using a microemulsion as a pore former. Background Art

[0002] Porous polymer materials have become a hot topic in materials science research due to their unique pore structure and excellent physical and chemical properties. In recent years, research in this field has made significant progress, especially in the preparation methods and functional expansion of materials. First, through innovative polymer technologies such as atom transfer radical polymerization (ATRP) and breath graph method, researchers have successfully prepared polymer materials with regular honeycomb pores. These methods allow precise control of pore size, porosity and pore arrangement to meet different application requirements. In addition, functional expansion is another important direction of research on porous polymer honeycomb materials. By introducing sensitive components into the material, such as pH-sensitive polyaniline, researchers have developed smart materials that can respond to environmental changes, and so on.

[0003] Constructing porous structures in polymer materials has always been a hot topic for researchers. For example, Tan Chunlin et al. reported the use of emulsion polymerization to prepare polyethylene-supported PAMS polymer membranes using urea as a pore-forming agent (Acta Physico-Chimica Sinica 2011, 27(07), 1689-1694.doi:10.3866 / PKU.WHXB20110712); Dan Yu et al. reported the use of a mixture of propylene glycol, polyethylene glycol diacrylate (PEGDA) and pentaerythritol tetrakis(PETMP) as a porous polymer material precursor to prepare PEG porous polymers through free radical mediation (Chemical Engineering Journal, 470, 2023, 144078). However, these pore-forming agents are all chemical reagents, which are not only impossible to completely remove, but also pollute the environment and have high costs. It is worth mentioning that the reports on water droplets as pore-forming agents are mainly the breath plot method and solvent displacement method. For example, Chinese patent CN 104861791 A discloses a method for preparing a honeycomb structure transparent coating by a breathing method, in which a double hydrophilic end group polystyrene is first coated on the surface of a substrate, placed in a room temperature atmosphere with a relative humidity of 60% to 90%, and left to stand for a period of time until the solvent evaporates to obtain a honeycomb structure transparent coating. Chinese patent CN 115041148 A provides a functionalized cellulose monolithic column porous material and a preparation method thereof, in which a porous material is obtained by solvent replacement, in which the polymer is first dissolved, then the solvent is volatilized by cooling, and finally the original solvent is replaced by a propylene glycol solvent to obtain a porous material.

[0004] The breath plot method is a method of preparing porous polymer membranes by controlling the condensation of water vapor on the surface of a solution, while the solvent replacement method dissolves the polymer in a specific solvent and then gradually replaces it with another solvent that is insoluble or poorly soluble in the polymer. As the original solvent evaporates and the new solvent penetrates, the polymer forms a porous structure during the solvent replacement process. Summary of the invention

[0005] The present invention provides a new method for preparing a porous honeycomb polymer material, namely, a non-solvent phase separation method. The non-solvent phase separation method uses the incompatibility between different phases to form a porous structure. The porous honeycomb polymer material prepared by non-solvent phase separation can not only show unique advantages in the fields of biosensing, drug controlled release and environmental monitoring, and show excellent electrochemical properties in the field of energy storage, but can also be applied to the fields of semi-solid, solid lithium ion, sodium ion batteries, etc. The method is a simple, green, controllable method for preparing a porous honeycomb polymer material with commercial application potential.

[0006] Description of the technical solution of the present invention:

[0007] Microemulsion is introduced as a pore-forming agent into the polymer polyvinylidene fluoride hexafluoropropylene (PVDF-HFP), and the microemulsion is composed of a mixture of deionized water and glycerol. PVDF-HFP is difficult to dissolve in both deionized water and glycerol solutions. The molecular chain of glycerol contains three polar hydroxyl groups, which are miscible with deionized water and hygroscopic. In addition, the polar bond hydroxyl group and the CF bond in PVDF-HFP are easy to form hydrogen bonds, thus forming a "core-shell" structure in which glycerol encapsulates deionized water and PVDF-HFP encapsulates glycerol.

[0008] By adjusting the amount of non-solvent microemulsion introduced, the pore size and pore volume of the pore structure can be controlled. In addition, microemulsion has a spontaneous coagulation phenomenon. By adjusting the stirring speed, the dispersion of the microemulsion in the gel solution can be controlled. Studies have found that the faster the stirring speed, the smaller the microemulsion droplets are dispersed, and the smaller the polymer pores obtained; on the contrary, the slower the stirring speed, the larger the pores obtained by the coagulation of the microemulsion.

[0009] Film-forming process: Since deionized water is incompatible with polymer PVDF-HFP, the free flow of deionized water is restricted by the coating layer, so that deionized water can exist stably and orderly, becoming a template for the solidifying polymer solution. At the same time, the evaporation of the solvent in the casting liquid increases the viscosity of the polymer, thereby effectively fixing the deionized water. When the casting liquid undergoes a phase separation process to form a solid film, the deionized water in the film evaporates completely, and a porous honeycomb polymer material can be obtained.

[0010] The specific steps of the technical solution of the present invention are:

[0011] (1) 0.5±10% of polyvinylidene fluoride hexafluoropropylene is fully dissolved in 7±10% of N-methylpyrrolidone, and 0.2-0.4 parts of microemulsion are added. The stirring speed of the stirrer is controlled at 100-1500 r / min and stirred until the various phases of the sol solution are uniformly mixed.

[0012] (2) The sol solution is directly cast into a glass-based container, first evaporated at room temperature, and then transferred to a vacuum drying oven for evaporation, thereby obtaining a porous honeycomb polymer material.

[0013] The microemulsion is composed of a mixture of deionized water and glycerol, and the mixing ratio is (10-50):35.

[0014] The evaporation time at room temperature is 10-480 min, preferably 60-360 min; the evaporation time in a vacuum drying oven is 1-48 h, preferably 6-24 h; the vacuum evaporation temperature is set to 50-200° C., preferably 80-150° C.

[0015] Technical features and beneficial effects of the present invention:

[0016] (1) The phase separation method is adopted to introduce the microemulsion as a pore former into the polymer PVDF-HFP, and the liquid phase of the microemulsion and the gel phase of the polymer PVDF-HFP are separated by utilizing the different volatilization temperatures of each solvent. Compared with the breath diagram method, the amount of the pore former introduced in the present invention is precisely controlled; in addition, compared with the solvent replacement method, the introduction of unnecessary impurities is avoided. The present invention adopts a phase separation method to achieve the regulation of pore size and a more uniform pore arrangement.

[0017] (2) The microemulsion is dispersed in the polymer PVDF-HFP gel by mechanical stirring, and porous polymer materials with different pore sizes are obtained by adjusting the stirring speed. Microemulsion has a spontaneous coagulation phenomenon. By controlling the rotation speed, the faster the speed, the more pores there are and the smaller the pore size. On the contrary, the slower the speed, the fewer pores there are and the larger the pore size. At the same time, the pore structure can also be regulated by the amount of microemulsion, that is, by controlling the stirring speed and the amount of pore-forming agent, the pore size and porosity can be easily regulated experimentally.

[0018] (3) Porous honeycomb polymer materials. Under optimized conditions, the mesoporous structure can be 2.4 nm and 3.8 nm, the micron-scale pore structure can have a pore size of about 5 μm, and the specific surface area can be 1395 cm 2 g -1 , the pore volume is 0.7374cm 3 g -1 .

[0021] (4) The preparation of porous honeycomb polymer materials is environmentally friendly, green, easy to obtain, and low-cost. NMP solvent, propylene glycol, and deionized water have little harm to the environment and are relatively environmentally friendly.

[0022] (5) Compared with the traditional method, the porosity of the porous honeycomb polymer material prepared by the present invention is increased by 30%. The material preparation process cost of the present invention is reduced by 35%, the production cycle is shortened by 80%, and it is easy to quickly realize commercial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a SEM image of the porous honeycomb polymer PVDF-HFP / DI-100 material prepared in the present invention;

[0024] Figure 2 This is a SEM image of the porous honeycomb polymer PVDF-HFP / DI-500 material prepared in the present invention;

[0025] Figure 3 This is a SEM image of the porous honeycomb polymer PVDF-HFP / DI-1000 material prepared in the present invention;

[0026] Figure 4 This is the SEM image of the porous honeycomb polymer PVDF-HFP / DI-1500 material prepared in the present invention. DETAILED DESCRIPTION

[0027] The present invention is further described in detail below through specific implementation cases. Unless otherwise specified, all raw materials and reagents of the present invention are raw materials and reagents from the conventional market.

[0028] Embodiment 1:

[0029] Preparation of porous honeycomb polymer PVDF-HFP / DI-1000 material:

[0030] First, 0.5 g of PVDF-HFP was dissolved in 7 mL of NMP solvent and stirred at 50 °C for 60 min at a stirring speed of 50 r min. -1 After cooling to room temperature, the microemulsion (300 μL of deionized water and 350 μL of glycerol) was introduced under stirring for 360 min at a stirring speed of 1000 r min. -1 Then, the sol solution was directly cast into a glass-based container, evaporated at room temperature for 120 min, and transferred to a vacuum drying oven for evaporation for 12 h. The temperature of the vacuum drying oven was set at 120° C., and finally a porous honeycomb polymer material was obtained.

[0031] Embodiment 2:

[0032] Preparation of porous honeycomb polymer PVDF-HFP / DI-100 material:

[0033] Example 2 provides a method for preparing a porous honeycomb polymer PVDF-HFP / DI-100 material. Compared with Example 1, the difference is that the stirring speed after the microemulsion is introduced is changed. The stirring speed is 100 rmin -1 The remaining steps are consistent with implementation 1.

[0034] Embodiment 3:

[0035] Preparation of porous honeycomb polymer PVDF-HFP / DI-500 material:

[0036] Example 3 provides a method for preparing a porous honeycomb polymer PVDF-HFP / DI-500 material. Compared with Example 1, the difference is that the stirring speed after the microemulsion is introduced is changed. The stirring speed is 500 rmin -1 The remaining steps are consistent with implementation 1.

[0037] Embodiment 4:

[0038] Preparation of porous honeycomb polymer PVDF-HFP / DI-1500 material:

[0039] Example 4 provides a method for preparing a porous honeycomb polymer PVDF-HFP / DI-1500 material. Compared with Example 1, the difference is that the stirring speed after the microemulsion is introduced is changed. The stirring speed is 1500 r min -1 The remaining steps are consistent with implementation 1.

[0040] Table 1: BET test data characterization of porous materials under different stirring speeds

[0041]

[0042] Table 1 reveals the BET test data of porous materials under different stirring speeds. With the increase of stirring speed, the pore size, pore volume and specific surface area of ​​PVDF-HFP have a significant increasing trend. According to the scanning electron microscope (SEM) images, it is found that the stirring speed is 1500 r min -1 When the pore size distribution on the surface of the porous material is uneven, the stirring speed is 1000 r min -1 The pore size of the porous material is relatively uniform.

[0043] Embodiment 5:

[0044] Compared with Example 1, the difference is that the amount of deionized water introduced into the mixed solvent for preparing the porous honeycomb polymer material is changed to 100 μL, and the other steps are consistent with Example 1.

[0045] Embodiment 6:

[0046] Compared with Example 1, the difference is that the amount of deionized water introduced into the mixed solvent for preparing the porous honeycomb polymer material is changed to 200 μL, and the other steps are consistent with Example 1.

[0047] Embodiment 7:

[0048] Compared with Example 1, the difference is that the amount of deionized water introduced into the mixed solvent for preparing the porous honeycomb polymer material is changed, and the amount of deionized water is 400 μL. The remaining steps are consistent with Example 1.

[0049] Embodiment 8:

[0050] Compared with Example 1, the difference is that the amount of deionized water introduced into the mixed solvent for preparing the porous honeycomb polymer material is changed to 500 μL, and the other steps are consistent with Example 1.

[0051] Table 2: BET test data characterization of porous materials with different amounts of deionized water in microemulsion

[0052]

[0053] Table 2 reveals the BET test data characterization of porous materials with changing the amount of deionized water in the microemulsion. As the amount of deionized water introduced increases, the pore size, pore volume and specific surface area of ​​PVDF-HFP have a significant increasing trend. However, when 500 μL of deionized water is introduced, the pore size, pore volume and specific surface area show a decreasing trend, which may be related to the collapse of the pore structure.

[0054] Comparative Example 1:

[0055] Compared with Example 1, Comparative Example 1 is different in that the pore-forming agent introduced into the polymer PVDF-HFP sol solution is changed to polyvinyl pyrrolidone (PVP), and the other steps are consistent with Example 1.

[0056] Comparative Example 2:

[0057] Compared with Example 1, Comparative Example 2 is different in that the pore-forming agent introduced into the polymer PVDF-HFP sol solution is changed to polystyrene spheres (PS), and the other steps are consistent with Example 1.

[0058] Comparative Example 3:

[0059] Compared with Example 1, Comparative Example 3 is different in that the surfactant introduced into the polymer PVDF-HFP sol solution is changed to sodium dodecyl sulfate (SDS), and the remaining steps are consistent with Example 1.

[0060] Comparative Example 4:

[0061] Compared with Example 1, Comparative Example 4 is different in that the surfactant introduced into the polymer PVDF-HFP sol solution is changed to polysorbate, and the other steps are consistent with Example 1.

[0062] Table 3: Effects of different types of pore-forming agents on polymer pores

[0063]

[0064] As shown in Table 3, the effects of different types of pore-forming agents on polymer pores were investigated. Unlike deionized water, chemical reagents can be used to form pores, but their pore distribution is not ideal. In addition, chemical reagents are difficult to remove from polymers and may leave residues. The preparation process of chemical reagents is relatively complicated, the production cost is high, and it is easy to pollute the environment.

Claims

1. A method for preparing a porous honeycomb polymer material, characterized in that: The method comprises the following steps: (1) Dissolve (0.5±10%) of polyvinylidene fluoride hexafluoropropylene in (7±10%) of N-methylpyrrolidone, add 0.2-0.4 of microemulsion, and stir at a stirring speed of 100-1500 r / min until all phases of the sol solution are uniformly mixed; (2) The sol solution is directly cast into a glass-based container, first evaporated at room temperature, and then transferred to a vacuum drying oven for evaporation to obtain a porous honeycomb polymer material; The microemulsion is composed of a mixture of deionized water and glycerol, and the mixing ratio is (10-50):35.

Citation Information

Patent Citations

  • Preparation method of transparent coating in honeycomb structure

    CN104861791A

  • Functionalized cellulose monolithic column porous material as well as preparation method and application thereof

    CN115041148A